2017
DOI: 10.1002/mop.30862
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency rectifier (5.2 GHz) using a Class‐FDickson charge pump

Abstract: This article presents a 5.2 GHz high‐efficiency rectifier, based on a Class‐F Dickson charge pump, for use in RF energy harvesting systems. A single‐stage Dickson charge pump with two Schottky diodes was adopted to produce a high‐output DC voltage. A harmonic source‐pull simulation was conducted to optimize the third harmonic impedance for the Class‐F harmonic termination. The proposed scheme is verified by designing and implementing a hybrid Class‐F Dickson charge pump for the 5.2 GHz band using two Schottky … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In this study, higher power conversion efficiency was obtained with lower load resistance value. 10 5 Note: Bold values are used to specifically indicate that the work in this article provides the same efficiency at lower voltages than the above work (50 one).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, higher power conversion efficiency was obtained with lower load resistance value. 10 5 Note: Bold values are used to specifically indicate that the work in this article provides the same efficiency at lower voltages than the above work (50 one).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most widely known RF rectifier circuits is the Dickson rectifier . The circuit, which can basically respond to low current and voltage, provides achieving high power conversion efficiency and high DC voltage over the output load . In addition to being practical and simple, Dickson rectifier circuits are widely preferred because they are suitable for being developed .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since RF–DC converters have been applied to various sensors that acquire energy or information for the operation from the input RF signal in addition to the MPT systems, a lot of previous studies of various aspects can be found [9,10,11,12,13,14,15,16,17]. Harmonic termination can be used to improve the conversion efficiency of the RF–DC converter based on the Schottky diode [9,10,11,12,13,14,15,16]. The authors in [9] realized a class-C operation at 2.45 GHz was realized using a shunt diode with short-circuited second and third harmonics, and reported an efficiency of 72.8% and an output voltage of 1.91 V using an input power of 8 dBm with a load resistance of 742 Ω.…”
Section: Introductionmentioning
confidence: 99%
“…The Rx consists of a 1×5 rectenna array that receives RF signals and converts them from RF to dc. A voltage doubler based on single-stage class-F structure was applied to maximize the conversion efficiency[31]. A 2-section input matching network for the individual rectifier based on a series transmission line and an open stub was designed for class-F operation and fundamental impedance matching.…”
mentioning
confidence: 99%